Superclay Creation / Nur Akma Shuhada Mohd Zamro... [et al.] - Mohd Zamro, Nur Akma Shuhada; Muhammad Nazim, Nur Fatihah; Ibrahim, Noor Arifah; Ramli, Suhailah; Wan Mohd, Wan Norhakimah (2021)
We are creating safe and edible modelling clays for toddlers and kids. We choose this product because we always convince that nowadays many parents are searching for modelling clays that free from dangerous chemical ingredients for their children as most of the modelling clays that are available in the market containing health and safety issues. Hence, we are here to provide organic modelling clays that have been confirmed free from hazardous ingredients. Moreover, our company also providing a small childcare service centre for customers that come to our store. We produce three types of packaging which are 100 g, 300 g and 500 g. The price for 100 g, 300 g and 500 g are RM 8.00, RM 22.00, RM 35.00 respectively. We also sell product in bundle such as trial pack, happy pack and fun pack for RM 15.00, RM 50.00 and RM 40.00 respectively. For our childcare service, we charge RM 25.00 for 1-hour service, 2-hours for RM 40.00 and 3-hours for RM 50.00. The price of our products are comparable with our quality of products. We offer price reduction with every packs. This will attract customer to buy the package because it provides a lot of things at a lower price. Other than that, we believe that by providing childcare service may assist the parents out there that have a busy life and works, but want to let their children playing at our store without having to worry about the children’s safety. The business venture had started on 9th September 2019. We only need 5 people which are ourselves to start the business and fill the following positions in our company. The positions are general manager, administration manager, marketing manager, operation manager and financial manager. Everyone has their own parts and roles in order to build our company. Every position is given to each person that are expert in that field. We choose Negeri Sembilan to open our clay premise which is located at 340, Jalan Bandar Senawang 1, Pusat Bandar Senawang, 70450 Seremban, Negeri Sembilan. Toysrus, Taska Iman An-Nur and R.E.A.L Kids are our competitors which located not far away from our premise. All of them have their own strengths and weaknesses. For example, Toyrus provide high quality toys, Taska Iman An-Nur provide childcare service per day and R.E.A.L Kids also provide childcare service per day. However, their weaknesses are because of their expensive price for services or products and some of their staffs are not friendly.